Zyxin mediation of stretch-induced gene expression in human endothelial cells - Wójtowicz, Agnieszka; Babu, Sahana Suresh; Li, Li; Gretz, Norbert; Hecker, Markus; Cattaruzza, Marco (Circulation research, 2010)
Rationale: - - Prolonged exposure to enhanced stretch, such as in hypertension, triggers endothelial dysfunction, a hallmark of pathological vascular remodeling processes. Despite its clinical relevance, little is known about stretch-induced gene expression in endothelial cells. - - Objective: - - Here, we have characterized a new stretch-inducible signaling pathway and the subsequent changes in endothelial gene expression in response to stretch. - - Methods and Results: - - Using human primary endothelial cells, we observed that the protein zyxin translocates from focal adhesions to the nucleus solely in response to stretch. There, it orchestrates complex changes in gene expression by interacting with a novel cis-acting element found in all zyxin-regulated genes analyzed so far. By way of DNA microarray pathway analyses, stretch-induced changes in endothelial cell gene expression were systematically explored, revealing that zyxin mainly regulates proinflammatory pathways. - - Conclusions: - - Stretch appears to be an important factor in the development of endothelial dysfunction with zyxin as a potential therapeutic target to interfere with these early changes in endothelial cell phenotype.
Originally published 12 Aug 2010
Gesehen am 21.03.2024